VD_FINDINFO HC / 2010 / 94 vom 22. Februar 2010 - VD Tribunal cantonal (2010)
APPEL EN CAUSE, ACTION RÉCURSOIRE, REPRISE DE DETTE EXTERNE, ATTRACTION DE COMPÉTENCE | 176 al. 1 CO, 176 CO, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 83 al. 1 CPC, 83 al. 1 let. a CPC, 83 CPC, 84 al. 3 CPC, 84 CPC, 85 CPC, 7 al. 1 LFors